PERANAN PENGGUNAAN MEDIA DALAM PENGEMBANGAN PELAYANAN KONSELING KELUARGA TERHADAP TANTANGAN KEMAJUAN ILMU PENGETAHUAN DAN TEKNOLOGI (IPTEK) - Santoso, Joko (Shift Key : Jurnal Teologi dan Pelayanan, 2017)
The reality of life in this era has an impact that make us aware the severity of the challenges faced. Multi-dimensional crises have plagued every aspect of human life and add to the complexity of life's problems. Many people fear, despair and hopelessness. Moreover, the fragility of family relationships Â and helplessness in building togetherness is fading. In response to this condition, the presence of family counseling services is a solution in giving answers. Given the gulf between family members is widespread. Both caused by the busyness and density of the activities of individuals, which resulted in the difficulty of socializing. So, to still be able to establish and build relationships Â that are strong and qualified, the communication media take a big role in it. Keywords : Technology, Family Counselling, Development.